2013
DOI: 10.1007/s11367-013-0614-0
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle greenhouse gas emissions of blended cement concrete including carbonation and durability

Abstract: Purpose Blended cements use waste products to replace Portland cement, the main contributor to CO 2 emissions in concrete manufacture. Using blended cements reduces the embodied greenhouse gas (GHG) emissions; however, little attention has been paid to the reduction in CO 2 capture (carbonation) and durability. The aim of this study is to determine if the reduction in production emissions of blended cements compensates for the reduced durability and CO 2 capture.Methods This study evaluates CO 2 emissions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 25 publications
1
115
0
2
Order By: Relevance
“…The traffic detour is considered taking into account the average daily traffic of 8500 vehicles/day, where trucks comprise 10% of vehicles and a detour distance of 2.9 km. On the other hand, the fixation of the CO 2 by the concrete is a widely studied fact [31,32] that has been considered in the bridge studied.…”
Section: Use and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…The traffic detour is considered taking into account the average daily traffic of 8500 vehicles/day, where trucks comprise 10% of vehicles and a detour distance of 2.9 km. On the other hand, the fixation of the CO 2 by the concrete is a widely studied fact [31,32] that has been considered in the bridge studied.…”
Section: Use and Maintenancementioning
confidence: 99%
“…In this case, the bridge will be destroyed, after which all the wastes will be transported to a sorting plant where the concrete and steel will be separated. The concrete will be crushed and transported to a landfill and in this way, the complete carbonation of the concrete [32] and thus a higher fixation of CO 2 is assured. Seventy-one per cent of the steel will be recycled and in this way, the life-cycle of the bridge ends.…”
Section: End Of Lifementioning
confidence: 99%
“…They concluded that the intensity of CO 2 emissions gradually decreases as Portland cement (up to 15 to 20%) is replaced by complementary cementitious materials. García-Segura et al (2014) sought to determine if the reduction in emissions of cements mixed with fly ash and blast furnace slag compensates for the reduction of their durability and their carbon capture by carbonation. They evaluated a reinforced concrete column during its life time and after its demolition and reutilization, having gravel as filling material.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…Kim et al (2016) If concrete mix and raw material suppliers were carefully selected, it can be obtained a reduction of 34% in the emission of CO 2 and 1% in the costs Park et al (2012) CO 2 emissions increase linearly with the compressive strength of the concrete; to similar strengths, the concrete produced in the winter presented an increase of approximately 5% in the CO 2 emissions Santoro and Kripka (2016) Higher strength concrete will produce a greater amount of CO 2 ; the CO 2 emissions during transport are significant Choi et al (2016) For smaller loads the increase of the transversal area of concrete is more advantageous for the eduction of O 2 emissions, and for greater loads the increase of the steel profile produces a more sustainable solution Berndt (2015) The use of smaller resistances is advantageous in relation to CO 2 emissions; the choice of the concrete mixture strongly influences the magnitude of the CO 2 emissions Yang et al (2015) The intensity of CO 2 emissions gradually decreases as Portland cement is replaced by complementary cementitious materials (up to 20%) García-Segura et al (2014) In comparison to Portland cement, despite the reduction in CO 2 capture and life time, 80% blast furnace slag cement emitted 20% less CO 2 per year Cabello et al (2016) To reduce the environmental impact generated by a structure, the focus should be on phases of production of raw materials, transportation and production of concrete Oliveira et al (2014) It is not appropriate to base decisions on the emissions of concrete solely on the strength of the concrete and the type of cement used, since the variations are significant Paya-Zaforteza et al (2009) Minimization of embedded CO 2 emissions and economic cost seem to be highly related Park et al (2013) Reducing the amount of steel and increasing the amount of concrete can be an effective way to reduce the structural costs and CO 2 emissions of columns Habert and Roussel (2009) It is also possible to combine cement replacement and increase mechanical strength Possan et al (2016) Concrete during its life time can absorb from 40 to 90% of CO 2 emitted in the manufacturing process; the absorption of CO 2 is directly proportional to the surface area of concrete exposed to CO 2 , and influenced by the type of cement and resistance to concrete. Park et al (2014) Increasing the strength of the structural materials used is more efficient in reducing CO 2 emissions and costs than increasing the quantities of structural materials used Collins (2013) If carbonation is ignored, emission estimates can be overestimated by up to 45% depending on the strength of the concrete that was used as well as the type of construction application that incorporates recycled concrete during the second generation Yepes et al (2012) CO 2 emissions and costs are closely related.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…The basic prices and emissions considered, given in Table 2, were obtained from the 2013 BEDEC ITEC database of the Institute of Construction Technology of Catalonia (BEDEC, 2013). Concrete unit price and CO 2 emissions were determined from each mix design, including transport and placing (García-Segura et al, 2014). Concerning the plasticizer used, CO 2 emissions were those given by the European Federation of Concrete Admixtures Associations, since it distinguishes between plasticizer (EFCA, 2006a) and superplasticizer (EFCA, 2006b).…”
Section: Objective Functionsmentioning
confidence: 99%